2008
DOI: 10.1002/jcp.21356
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 (CYP) 2J2 gene transfection attenuates MMP‐9 via inhibition of NF‐κβ in hyperhomocysteinemia

Abstract: Hyperhomocysteinemia (HHcy) is associated with atherosclerotic events involving the modulation of arachidonic acid (AA) metabolism and the activation of matrix metalloproteinase-9 (MMP-9). Cytochrome P450 (CYP) epoxygenase-2J2 (CYP2J2) is abundant in the heart endothelium, and its AA metabolites epoxyeicosatrienoic acids (EETs) mitigates inflammation through NF-kappabeta. However, the underlying molecular mechanisms for MMP-9 regulation by CYP2J2 in HHcy remain obscure. We sought to determine the molecular mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…On the other hand, 20-HETE, an eicosanoid produced by P450 -hydroxylases, has been reported to have a detrimental effect on the heart (Chábová et al, 2007;Lv et al, 2008;Minuz et al, 2008), leading to cardiac hypertrophy and heart failure (Bao et al, 2011). Mechanistically, these opposing effects of P450-derived AA metabolites are mediated through several intracellular signaling cascades that have been implicated in development and/or progression of cardiovascular toxicity, e.g., nuclear factor B, mitogen-activated protein kinase, and matrix metalloproteinase-9 (Node et al, 1999;Sun et al, 1999;Elbekai and El-Kadi, 2006;Ishizuka et al, 2008;Moshal et al, 2008). As an important player affecting the balance between P450-derived AA metabolites, soluble epoxide hydrolase (sEH) enzyme hydrolyzes the cardioprotective metabolites EETs to biologically less active metabolites, dihydroxyeicosatrienoic acids (DHETs) (Imig et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, 20-HETE, an eicosanoid produced by P450 -hydroxylases, has been reported to have a detrimental effect on the heart (Chábová et al, 2007;Lv et al, 2008;Minuz et al, 2008), leading to cardiac hypertrophy and heart failure (Bao et al, 2011). Mechanistically, these opposing effects of P450-derived AA metabolites are mediated through several intracellular signaling cascades that have been implicated in development and/or progression of cardiovascular toxicity, e.g., nuclear factor B, mitogen-activated protein kinase, and matrix metalloproteinase-9 (Node et al, 1999;Sun et al, 1999;Elbekai and El-Kadi, 2006;Ishizuka et al, 2008;Moshal et al, 2008). As an important player affecting the balance between P450-derived AA metabolites, soluble epoxide hydrolase (sEH) enzyme hydrolyzes the cardioprotective metabolites EETs to biologically less active metabolites, dihydroxyeicosatrienoic acids (DHETs) (Imig et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Image analysis of the protein bands was performed using UMAX PowrLock II (Taiwan). The protein expression intensity was assessed by integrated optical density [14].…”
Section: Western Blot Analysismentioning
confidence: 99%
“…EETs may be PPARγ ligand [16], and PPARγ agonists attenuated Ang II-induced inflammation via NF-κB pathway [48]. Additionally, EETs exerted anti-inflammatory effect via inhibiting IκBα degradation and NF-κB translocation [15]. Our experiments suggested a crucial role of PPARγ-NF-κB pathway in the anti-inflammatory effect of exogenous EETs administration and CYP2J2 overexpression.…”
Section: Discussionmentioning
confidence: 61%
“…Studies showed that PPARγ ligands suppress inflammation by inhibiting the activation of nuclear factor κB (NF-κB), activator protein 1 (AP-1) and signal transducers and activator of transcription (STAT). Moshal et al [15] reported that CYP2J2 transfection or exogenous 8,9-EET addition phosphorylated AKT and attenuated homocysteine-induced MMP-9 activation by inhibiting NF-κB nuclear translocation, NF-κB-DNA binding, and IκBα activation. Further studies indicated that PPARγ is an effector of EETs, as blocking PPARγ by GW9662 abolished EET/AUDA-mediated anti-inflammatory effect [16].…”
Section: Introductionmentioning
confidence: 99%